Causes of Hyperemesis Gravidarum - Israini Suriati; Yusnidar Yusnidar (Politeknik Kesehatan Kementerian Kesehatan Semarang, 2021)
Hyperemesis Gravidarum is a common symptom and is often seen in the first trimester of pregnancy, which occurs in 60-80% of primigravida and 40-60% of multigravida. Nausea usually occurs in the morning, but can occur at any time of the night. These symptoms approximately occur after 6 weeks after the first day of the last menstrual period and last for approximately 10 weeks. The incidence of Hyperemesis Gravidarum is influenced by the knowledge of pregnant women, the age of pregnant women and gravidas at Batara Guru Belopa Regional Hospital in 2020. The type of research used is quantitative research with cross sectional design. The sample in this study were pregnant women who experienced hyperemesis gravidarum, both those who experienced grade I hyperemesis, Level II and level III who came to visit the Batara Guru Belopa Regional Hospital for the March - June 2020 period were 47 pregnant women. The results of the research conducted at Batara Guru Belopa, Luwu Regency, showed that in general knowledge, age and gravidity had a significant relationship with the incidence of hyperememesis gravidarum in Batara Guru Belopa Regional Hospital, where the chi-square value count was ≥ X2 table. In the knowledge variable with the occurrence of hyperemesis gravidarum, it is a value of 0.002 and in the age variable the value is 0.003, while the gravid variable with the occurrence of hyperemesis gravidarum is a value of 0.001